Immunotherapy in oral cancer - Sunil Paramel Mohan; Manoj K Bhaskaran; Ashford L George; Abhilash Thirutheri; Maya Somasundaran; Anegh Pavithran (Wolters Kluwer Medknow Publications, 2019)
Immunotherapy is one of the newer entities which is promising, at least can be very much helpful as an adjuvant therapy. This newer modality of the treatment in the field of cancer treatment may be the fourth pillar supporting surgery, chemotherapy, and radiotherapy. Careful selection of patient is the key for success of immunotherapy, which is based on patient's immunological contexture. This review aimed to present the fundamental aspects of tumor immunity and immunotherapy, focused on oral squamous cell carcinoma.